Waste-Wise Education: Impact on Zero Waste Awareness and Practices - Dina, Dina -; Fillaeli, Annisa; Jayanti, Asti Aulia (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
This study aimed to determine how waste-aware education affected the zero-waste consciousness and behaviors of chemical education students. A one-group, pretest-posttest design was implemented using a sample of 70 first-year students enrolled at Yogyakarta State University. The students were provided with workshop materials about waste management at temporary storage sites (TPS) and final processing sites (TPA) in Yogyakarta, as well as waste issues that have arisen with the advancement of science and technology. After completing two meetings of the workshop, they were assigned a series of consultations and a final project. In order to gather information, questionnaires, and portfolios were utilized. The findings of the study indicated that waste-aware education can enhance students' zero-waste awareness and practices. The sig value of 0.000 for the Wilcoxon test on zero waste awareness indicated a substantial increase. Similarly, the t-test conducted on zero waste practices yielded a significance value of 0.000, indicating that the provision of waste-aware education had a noteworthy impact. Students were, on the whole, enthusiastic about spreading the zero-waste philosophy throughout society.